EFFECT OF INCREASED DOSES OF THREE MUSTARD OIL AND TWO TEA TREE OIL FORMULATIONS ON CIMBEX QUADRIMACULATA - Güral, Yunus; Özgen, İnanç; Hassan, Errol; Ardahanlı, Metehan (My University, 2022)
The female of almond saw fly lays eggs in and on plant tissue in spring and summer time, once the eggs hatch the young larvae start to feed on the almond leaves, causing defoliation of the trees depending on the population levels. In this study; It is aimed to evaluate the effects of three mustard oil and two tea tree oil formulations used against larval stages of the almond insect pest Cimbex quadrimaculata (Müller, 1766) (Hymenoptera: Cimbicidae). The five botanical formulations were tested under laboratory conditions, using dipping method of 3 cm diameter almond leaves, which, were dipped five different doses and air dried before being offered to the first larval stages, including negative control using only water. Feeding and mortality rates of 240 larvae in total were followed up until the end of the pupal period and recorded. It was determined that the increased dose of the formulation containing mustard oil + allylisothiocyanate monoethanolamine dissolved in non-ionic surfactants was more effective than other botanical formulations. The results of this study are important for almond organic pest management.
Keywords: Cimbex quadrimaculata; botanical formulations; increased dose; insecticidal effects.